THE RELEVANCE OF THE DEVELOPMENT OF DIGITAL TRANSFORMATION IN THE SYSTEM OF PHARMACEUTICAL SANOLOGY IN OCCUPATIONAL DISEASES - Андрей Георгиевич Петров; Ольга Владимировна Хорошилова; Сергей Николаевич Филимонов; Николай Иванович Панев; Виктор Андреевич Семенихин; Елена Борисовна Григорьева (Медицина в Кузбассе, 2024)
Human health is an indicator of working conditions, the state of the environment, the current state of technology and technology, as well as the effectiveness of health care. The high rates of occupational morbidity in the coal industry and the insufficient effectiveness of measures taken to prevent it in recent years have not satisfied either owners, employees, or the state. One of the priority and relevant directions of modern pharmaceutical science is the organization of the prevention of occupational diseases in the system of specialized pharmaceutical care for employees of the coal industry. However, these issues have not been reflected in previous studies. The above indicates that the development of pharmacoprophylactic programs in the system of pharmaceutical sanology within the framework of medicine and occupational safety using modern digital technologies is currently extremely relevant in solving the problem of occupational diseases, preserving the health of the working population in the industrialized regions of Russia, in particular Kuzbass. Modern information technologies in medicine and pharmacy are assistive technologies that support research in the field of healthcare, medical and pharmaceutical practice, including treatment, recovery, disease prevention and public health promotion. The digital tools of modern medicine make it possible to make a breakthrough in the approach to the treatment and prevention of diseases. It should be emphasized that the paradigm of modern healthcare is an active role of a person in maintaining their health and life, taking into account the development of the movement towards forecasting, prevention and a healthy lifestyle, and requires new processes of using digital assisting tools based on accumulated experience and the formation of scientifically sound proposals to restart the process of implementing 4P approaches in Russian healthcare: disease prevention; disease prevention; personalized approach to the patient; participation and full understanding of the processes by the patient.